2017
DOI: 10.1021/acs.biochem.7b00101
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Induces Toxicity in HeLa Cells through Perturbation of Microtubule Polymerization by Binding to Tubulin at a Unique Site

Abstract: Berberine has been used traditionally for its diverse pharmacological actions. It exhibits remarkable anticancer activities and is currently under clinical trials. In this study, we report that the anticancer activity of berberine could be partly due to its inhibitory actions on tubulin and microtubule assembly. Berberine inhibited the proliferation of HeLa cells with an IC of 18 μM and induced significant depolymerization of interphase and mitotic microtubules. At its IC, berberine exerted a moderate G2/M arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…Besides the regulation of signal transduction pathways, the direct interaction of berberine with the cellular cytoskeleton may underlie its inhibitory effect on cell migration and cell proliferation. Recently, it has been demonstrated that berberine binds to VASP and inhibits actin polimerization 49 and it also binds to a single site of tubulin, inhibiting microtubule assembly and promoting depolimerization 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides the regulation of signal transduction pathways, the direct interaction of berberine with the cellular cytoskeleton may underlie its inhibitory effect on cell migration and cell proliferation. Recently, it has been demonstrated that berberine binds to VASP and inhibits actin polimerization 49 and it also binds to a single site of tubulin, inhibiting microtubule assembly and promoting depolimerization 50 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 58,59 ] Although, the mechanisms by which Ber exacerbated radiation mediated G2/M arrest is presently unclear however, a previous report suggests its ability to disrupt mitotic spindle leading to mitotic catastrophe. [ 57 ] It has also been shown earlier that Ber can exert a G2/M arrest via ATM‐Chk1 activation. [ 14 ] As suggested earlier, inhibition of Topoisomerase II activity might result in a mitotic catastrophe.…”
Section: Discussionmentioning
confidence: 85%
“…A healthy microtubule network is necessary for the completion of autophagic process. [ 56 ] Earlier, Ber has been shown to disrupt microtubule integrity [ 57 ] which might be a causative factor blocked autophagy leading to the accumulation of autophagosomes and lysosomes, although the exact mechanism requires further experimental evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction mixture was then subjected to centrifugation at 50 000 × g for 1 hour. The supernatant and pellet were collected separately, and the protein concentration in the supernatant was measured using Bradford assay …”
Section: Methodsmentioning
confidence: 99%